2021
DOI: 10.1088/1752-7163/abe5ca
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of SARS-CoV-2 infection by multicapillary column coupled ion mobility spectrometry (MCC-IMS) of breath. A proof of concept study

Abstract: There is an urgent need for screening of patients having a communicable viral disease to cut infection chains. We could recently demonstrate that MCC-IMS of breath is able to identify In uenza-A infected patients. With decreasing In uenza epidemic and upcoming SARS-CoV-2 infections we went on and also analysed patients with suspected SARS-CoV-2 infections. 75 patients, 34m, 41f, aged 64.4 ± 15.4 years, 14 positive for In uenza-A, 16 positive for SARS-CoV-2, the remaining 44 patients were used as controls. In o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 18 publications
0
37
1
Order By: Relevance
“…VOCs are usually required to be collected into a gas bag or gas bottle for subsequentially GC–MS analysis (Table 3 ). GC–MS analysis of breath VOC and blood metabolites has been proposed for COVID-19 diagnosis and research [ 29 , 59 61 ]. To improve biomarker discovery, SPME and needle trap device techniques were also proposed to couple with GC–MS for enhanced breath analysis in COVID-19 research [ 55 , 61 63 ].…”
Section: Ms-based Multidimensional Breath Analysismentioning
confidence: 99%
“…VOCs are usually required to be collected into a gas bag or gas bottle for subsequentially GC–MS analysis (Table 3 ). GC–MS analysis of breath VOC and blood metabolites has been proposed for COVID-19 diagnosis and research [ 29 , 59 61 ]. To improve biomarker discovery, SPME and needle trap device techniques were also proposed to couple with GC–MS for enhanced breath analysis in COVID-19 research [ 55 , 61 63 ].…”
Section: Ms-based Multidimensional Breath Analysismentioning
confidence: 99%
“…Some of the VOCs produced in a single cell line of the infective viruses H9N2, H6N2, and H1N1 appeared selective for each virus, but a plethora of several other non-specific VOCs were present ( 26 ). A study on breath analysis using multi-capillary column-ion mobility spectrometry showed that it is possible to discriminate between influenza A and SARS-CoV-2 infections based on the different VOC profiles, although specific VOCs were not identified ( 27 ). The authors suggested that dogs could be used to successfully discriminate SARS-CoV-2 infection from other infective diseases.…”
mentioning
confidence: 99%
“…In addition, infections by different influenza A virus subtypes result in disparate VOC patterns ( 21 ). Current data from several studies suggest that SARS-CoV-2 infections create a specific VOC pattern which could be used in diagnostics ( 22 , 37 , 39 , 40 ). Steppert et al analysed exhaled breath from persons infected by SARS-CoV-2 or influenza A virus and healthy people via multi-capillary column-ion mobility spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Steppert et al analysed exhaled breath from persons infected by SARS-CoV-2 or influenza A virus and healthy people via multi-capillary column-ion mobility spectrometry. They were able to discriminate between SARS-CoV-2, influenza A virus and controls in a few minutes which indicates that SARS-CoV-2 and influenza A virus infections can be distinguished by their differing VOC patterns ( 22 ). In summary, these data indicate that every viral infection creates its own specific VOC pattern and can therefore be discriminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation